Community Economic Empowerment Through Human Resources Development in Digital Marketing Implementation BUMDES and MSMEs in Sindanglaya - Silvy Sondari Gadzali; Rio Trihatmojo; Dwi Imel Octavia; Viona Fitaloka (Jurma : Jurnal Program Mahasiswa Kreatif, 2022)
Technological developments at this time have a lot of very rapid progress. So its existence greatly impacts various aspects and dimensions, including marketing and sales dimensions. Many business actors are starting to switch to the digital world and leaving traditional activities. This service is carried out to develop human resources to utilize digital marketing in marketing and selling their products. The activity was carried out using a participatory method with 3 stages, namely: planning, implementation, and evaluation. In the implementation process, marketing activities are carried out by applying the Facebook fan page and sales media using the Shoppe application. Using these digital marketing activities can provide benefits in the form of reducing promotional costs, being easily indexed by search engines, strengthening relationships with customers, helping to find the right target market, and adding credibility to the products being sold. The enthusiasm of successful business actors for this activity has an impact on the knowledge and insights that have been obtained so that their businesses can be marketed and sold online. With so expected product sales profits are expected to increase.